Resurrection iWitness - Powell, Doug (Nashville : B & H Publishing Group, 2012)
Comparable in style to the best-selling Ologies children's fantasy book series, Resurrection iWitness brings truth to the highly illustrated genre. This book gives evidence for the resurrection of Jesus Christ by using the easy-to-understand Minimal Facts argument. That means it relies only on the historical facts that almost all biblical scholars (including atheistic, Jewish, and liberal) accept and shows how only the biblical story of the resurrection can account for all these agreed-upon facts. Across 32 intensively designed pages (16 spreads acting as individual chapters) -- each containing information that is physically nested and must be actively opened to discover -- the reader investigates the story of Christ and weighs the evidence to determine its historical accuracy.
Keywords: Apologetics -- Non-fiction